GENRE PECULIARITIES OF THE LITERATURE OF THE NORMAN PERIOD (12TH 13TH CENTURIES) - Ivanova, Tetiana (Scientific Journal of Polonia University, 2023)
The period of French domination left an important mark on the later history of English literature, which, in some cases, is more common with the artistic devices and style of French literature of the Norman period than with the study of Anglo-Saxon literature, from which it was artificially divorced. The Norman conquest conditioned certain specific features of language development. The main one was the spread of three languages in the Kingdom of England – French among the ruling class, English among the broad masses of the population, and Latin in church affairs and administration. This affected the linguistic and genre character of English medieval literature.Methods used in the study: general scientific (analysis and synthesis, induction and deduction), methods of theoretical research (from abstract to concrete), historical method Among the feudal lords, the most popular genre was chivalric poetry, which was brought from France by trouver singer-poets. The most common manifestation of chivalric poetry was the rhyming chivalric novel, which reflected the customs of the upper feudal class, promoted heroic deeds, the code of chivalric morality, and examples of human virtues. The novels about King Arthur and the Knights of the Round Table became the most popular.